A Literature Review: Foreign Language Enjoyment Using Game-Based Learning (Wordwall) For Student Engagement And Speaking Proficiency - Situmorang, Lidya Cristina Febriani; Ratminingsih, Ni Made; Mahayanti, Ni Wayan Surya (Jurnal Locus Penelitian dan Pengabdian, 2025)
This literature review explores the intertwined roles of Foreign Language Enjoyment (FLE), game-based learning (GBL), student engagement, and speaking proficiency in the context of foreign language education. FLE has emerged as a vital affective factor that enhances language acquisition by fostering positive emotions. Game-based learning tools, especially Wordwall, have been shown to increase classroom engagement and reduce speaking anxiety by providing interactive and learner-centered experiences. The review summarizes the advantages of incorporating Wordwall into language learning, particularly in developing vocabulary and encouraging speaking practice. Additionally, it explores how enjoyment facilitates deeper engagement—behavioral, emotional, and cognitive—ultimately contributing to improved speaking proficiency.